Impacts of global environmental change drivers on non‐structural carbohydrates in terrestrial plants. (13th May 2020) - Du, Ying; Lu, Ruiling; Xia, Jianyang
Abstract: Non‐structural carbohydrates (NSCs, including soluble sugars and starch) are essential to support the growth and survival of terrestrial plants. Starch and sugars play different roles in multiple plant ecological functions such as drought tolerance, growth and plant defence, and several other processes which are being rapidly shaped by global environmental change. However, it is uncertain whether soluble sugars and starch show different responses across plant functional types, tissue types and treatment conditions (i.e. the intensity and duration of environmental variability) to global‐change drivers. Here based on a database of 275 plants (including 17 plant functional types), we conducted a meta‐analysis to examine the effects of elevated atmospheric CO2 concentration (eCO2 ), nitrogen (N) addition, drought and warming on NSCs and its components. We found NSCs responses to global environmental change were mainly driven by (a) soluble sugar changes in response to N addition and drought, as well as (b) starch changes in response to eCO2 and warming. The different responses between soluble sugars and starch were more evident under eCO2 and drought, especially in herbs or leaves. Interactive effects of multiple environmental change drivers on soluble sugars and starch were mainly additive. The divergent main and interactive effects on soluble sugars and starch depend on experimental conditions. For example, the starch responses to eCO2 and its interaction with N addition were the strongest in short‐term experiments. Overall, our study shows the divergent responses of soluble sugars and starch in terrestrial plants to different global environmental change drivers, suggesting a changed carbon sink–source balance in plants under future global changes. The findings also highlight that predicting plant functional changes into the future requires a mechanistic understanding of how NSCs and its components are linked to specific environmental change drivers. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article